THE PARADIGM OF THE FORMATION OF A NEW TECHNOLOGICAL STRUCTURE OF THE FOOD INDUSTRY, AGRICULTURE IN RUSSIA NORTH CAUCASUS FEDERAL DISTRICT AND THE STAVROPOL TERRITORY ON THE EXAMPLE OF THE DAIRY CASE - Andrey Khramtsov (Вестник Северо-Кавказского федерального университета, 2022)
In accordance with the Doctrine of Food Security of our country in the article the paradigm of the formation of a new sixth technological structure of the food industry, agriculture, for example dairy case.